ELITE SCHOOL POLICIES; SUPERIOR ISLAMIC SCHOOLS - Amaliyah Amaliyah (Edukasi Islami: Jurnal Pendidikan Islam, 2020)
This study aims to examine the policies of leading schools/madrasas in Indonesia, which have elitist tendencies and become reproductive forces rather than productive forces. This picture is evident from the community's view on identifying rich and poor schools, and even becoming a socioeconomic measure for the community. Furthermore, elite schools are seen as excellent schools that meet the quality standards of their graduates. The emergence of elite Islamic schools is at least motivated by several factors, including factors, ideology, social, historical, and psychology, as a response to problems in Islamic education that are always discussed by the world of education, where the tendency only functions in the spiritual. There are two formulations of this study's problem, namely, how does elitism emerge in leading schools/madrasas? Then, how to reconstruct the leading school/madrasa to guarantee access to education that is equitable for all children of the nation from all walks of life, especially among the poor? The results of this study, first, the elite schools get special treatment from the government by receiving block-grant subsidies and being given the freedom to collect school fees from parents/guardians of students. Second, reconstruction steps are needed to improve the education of the excellent schools/madrasas to be enjoyed equally by the entire community and educate all the nation's children.